2017
DOI: 10.1111/scd.12246
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an oral health educational intervention for individuals with special health care needs from a southern Brazilian city

Abstract: Providing a simple and short-term educational intervention to students with disabilities had a positive impact on their oral health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…Regularly attending the dentist enables provision of oral hygiene instructions and dietary guidelines, and the possibility of receiving preventive procedures such as the use of fluoride varnishes and pit and fissure sealants. Intervention studies reinforce the importance and effectiveness of regular and continuous oral health education among people with SHCN [11,20,27]. Another hypothesis is that people who make regular use of dental services may be those who have a greater self-care role in their oral health.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Regularly attending the dentist enables provision of oral hygiene instructions and dietary guidelines, and the possibility of receiving preventive procedures such as the use of fluoride varnishes and pit and fissure sealants. Intervention studies reinforce the importance and effectiveness of regular and continuous oral health education among people with SHCN [11,20,27]. Another hypothesis is that people who make regular use of dental services may be those who have a greater self-care role in their oral health.…”
Section: Discussionmentioning
confidence: 96%
“…This cross-sectional study was carried out between March and August 2015 and was nested in a clinical trial that assessed the effectiveness of an oral health education intervention to prevent oral diseases. More information can be obtained in the educational intervention article made with this sample [11].…”
Section: Study Setting and Populationmentioning
confidence: 99%
“…example, Hartwig et al (2017) maintained weekly motivation to ensure oral hygiene was part of daily routines in four sequential sessions. Witton et al (2017) found that regular demonstration and repetition enabled effective toothbrushing and therefore supported independent oral hygiene practice.…”
Section: 19 20mentioning
confidence: 99%
“…The extent to which caregivers and supporters are effective facilitators in health education for people with intellectual disabilities can vary considerably. Some studies reported they had a positive effect on acquiring and embedding learning (Bergström et al, 2013;Dunkley et al, 2017;Hartwig et al, 2017;Sandjojo et al, 2019). Dunkley et al (2017) found that care workers had a key role in helping to motivate and support participants to make and sustain changes to their diet and physical activity.…”
Section: 19 20mentioning
confidence: 99%
See 1 more Smart Citation